2018
DOI: 10.1002/aic.16360
|View full text |Cite
|
Sign up to set email alerts
|

Coupling brain perfusion screens and next generation sequencing to identify blood–brain barrier binding antibodies

Abstract: Antibodies that target the blood-brain barrier (BBB) in vivo are of particular interest for the treatment of neurological diseases. Here, we screened a phage display single-chain antibody (scFv) library by brain perfusion in an attempt to isolate scFv that target the rat BBB. After four rounds of screening, the resulting antibody pool remained highly complex and discrete clonal sampling did not identify any scFvs capable of binding to the rat BBB. Thus, the heavy chain CDR3 in the resulting pools was subjected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…10 However, unlike genomic and proteomic approaches in which the BBB target receptor is known, phenotypic screening requires downstream target receptor identification. 12 To date, phenotypic screening of large libraries in vivo 13,14 and in vitro 15,16 for new antibody-RMT pairs has shown limited success, with only a handful of new BBB targeting antibodies isolated. In vivo screening challenges include the finding that phage antibody libraries are plagued by high background recoveries masking relevant clones, 16 while antibodies identified from in vitro biopanning often do no not cross-react with in vivo antigens, due to potential alteration of protein expression profiles in culture.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 However, unlike genomic and proteomic approaches in which the BBB target receptor is known, phenotypic screening requires downstream target receptor identification. 12 To date, phenotypic screening of large libraries in vivo 13,14 and in vitro 15,16 for new antibody-RMT pairs has shown limited success, with only a handful of new BBB targeting antibodies isolated. In vivo screening challenges include the finding that phage antibody libraries are plagued by high background recoveries masking relevant clones, 16 while antibodies identified from in vitro biopanning often do no not cross-react with in vivo antigens, due to potential alteration of protein expression profiles in culture.…”
Section: Introductionmentioning
confidence: 99%
“…12 To date, phenotypic screening of large libraries in vivo 13,14 and in vitro 15,16 for new antibody-RMT pairs has shown limited success, with only a handful of new BBB targeting antibodies isolated. In vivo screening challenges include the finding that phage antibody libraries are plagued by high background recoveries masking relevant clones, 16 while antibodies identified from in vitro biopanning often do no not cross-react with in vivo antigens, due to potential alteration of protein expression profiles in culture. Further, human in vitro BBB models based on primary or immortalized BMECs are inherently leaky, limiting the effectiveness of functional transcytosis screens of antibody libraries.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, a variety of methods using NGS for antibody discovery have been developed. Most of the methods exclusively explore CDR-H3 repertoires 55 , 57 – 59 , 61 , 62 . The identified potential binders in NGS data are discovered using naïve approaches, including enrichment ranking or interrogation of antibody databases 55 62 .…”
Section: Discussionmentioning
confidence: 99%
“…It also implies that the combination of CDR-L3 and CDR-H3 offers higher diversities than CDR-H3 alone (Fig. S2D ), with increased numbers of potential binders when compared to the methods that explore CDR-H3 repertoires exclusively 55 , 57 – 59 , 61 , 62 .…”
Section: Discussionmentioning
confidence: 99%
“…NGS has previously been used for discovery of antibodies from phage display libraries (Ravn et al, 2010; Zhang et al, 2011; Ravn et al, 2013; Lopez et al, 2017; Yang et al, 2017; Stutz et al, 2018; Barreto et al, 2019). These studies have shown that compared with traditional screening, NGS enables discovery of more clones (Ravn et al, 2010; Ravn et al, 2013; Yang et al, 2017; Stutz et al, 2018), clones with higher affinity (Barreto et al, 2019), or clones binding functionally more interesting epitopes (Lopez et al, 2017; Stutz et al, 2018; Barreto et al, 2019). In many of these studies, the most enriched antibody sequences, against one or several proteins, although sometimes in a complex context (Zhang et al, 2011), have been recovered and used for downstream analysis.…”
Section: Discussionmentioning
confidence: 99%